FINANCIAL STRESS, SELF-EFFICACY AND FINANCIAL HELP-SEEKING BEHAVIOUR AMONG COLLEGE STUDENTS DURING PANDEMIC - Kasenda, Peggy G.H.; Kaparang, Grace F.; Pangemanan, Anthony; Ambalao, Shapely S. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Abstract: Psychological resilience has been challenged along with the pandemic and college students are vulnerable to experience financial stress. This study aims to analyze the financial stress, self-efficacy and financial help seeking behavior in college students during the pandemic. This cross-sectional design study, using a reliable online questionnaire and Spearman correlation as statistical treatment. The majority of participants experienced moderate financial stress, with high financial self-efficacy, did not seek any financial assistance, but willing to seek financial assistance. The results of the Spearman’s rho correlation test showed that financial stress had a significant weak positive relationship with the financial help seeking behavior (r=.120; p=.013<.05) and had a significant weak negative relationship with intention to seek financial help (r=-.269; p=.001<.05). Financial stress was not significantly correlated with financial self-efficacy. Finally, financial self-efficacy was not significantly correlated with financial help seeking behavior and intention to seek financial help. It is recommended for higher education institutions, especially the economics and business faculties to provide counseling on personal financial management for students who intended to seek financial assistance. Future research can focus on the factors that influence financial stress and how they can overcome it in both qualitative and quantitative approaches Abstrak: Ketahanan psikologis telah ditantang seiring dengan pandemi dan mahasiswa rentan mengalami tekanan finansial. Penelitian ini bertujuan untuk menganalisis stres keuangan, efikasi diri dan perilaku mencari bantuan keuangan pada mahasiswa selama pandemi. Studi desain cross-sectional ini, menggunakan kuesioner online yang andal dan korelasi Spearman sebagai perlakuan statistik. Mayoritas peserta mengalami stres keuangan sedang, dengan self-efficacy keuangan yang tinggi, tidak mencari bantuan keuangan, tetapi bersedia untuk mencari bantuan keuangan. Hasil uji korelasi Spearman’s rho menunjukkan bahwa stres keuangan memiliki hubungan positif lemah yang signifikan dengan perilaku mencari bantuan keuangan (r=.120; p=.013<.05) dan memiliki hubungan negatif lemah yang signifikan dengan niat mencari bantuan keuangan. bantuan (r=-.269; p=.001<.05). Stres finansial tidak berkorelasi signifikan dengan self-efficacy finansial. Akhirnya, self-efficacy keuangan tidak secara signifikan berkorelasi dengan perilaku mencari bantuan keuangan dan niat untuk mencari bantuan keuangan. Disarankan kepada institusi pendidikan tinggi khususnya fakultas ekonomi dan bisnis untuk memberikan penyuluhan tentang pengelolaan keuangan pribadi bagi mahasiswa yang hendak mencari bantuan keuangan. Penelitian di masa depan dapat fokus pada faktor-faktor yang mempengaruhi tekanan keuangan dan bagaimana mereka dapat mengatasinya baik dalam pendekatan kualitatif maupun kuantitatif